Implementation of the ResepKita Application as an Innovative Platform for Creating and Sharing Food and Beverage Recipes - Damar Pratama Ristadias Hariyanto; Ahmad Yani; Arya Restu Pratama; Syamil Syamil; Yaya Sudarya (Journal Collabits, 2025)
This research focuses on developing a web-based application designed to improve the management of food and beverage recipes in canteens. The application is built using PHP for the backend, MySQL for database management, and Bootstrap for a responsive user interface. The system helps canteen managers efficiently manage recipes, track inventory, and analyze menu preferences to optimize resource usage. Key features of the application include the ability to search for recipes based on ingredients, generate reports on popular and less popular menu items, and provide recommendations for stock management. The application was evaluated by testing its functionality with real-world data from canteen operations, showing its effectiveness in increasing operational efficiency and customer satisfaction. Future development will focus on integrating real-time inventory monitoring and expanding the application to support mobile devices for enhanced accessibility.